Teknik Pantomim Siswa Dalam Pembelajaran Kosakata Bahasa Arab (Neolectura, 2023)
Arabic is one of the foreign languages taught in various Indonesian educational institutions, starting from the Early Childhood Education level to tertiary institutions. The position of Arabic as the language of religion, science and language of international communication makes Arabic an important language to learn. Learning vocabulary (mufradat) is a person's initial foundation in learning Arabic. Good vocabulary mastery will form good Arabic language skills as well. There are various kinds of learning techniques used for learning objectives, one of which is the pantomime technique. This paper aims to describe pantomime techniques in learning Arabic vocabulary and to explain the influence of pantomime techniques in learning Arabic vocabulary. The method used in this research is library research through documentation techniques. From the results of the analysis of the literature review, the pantomime technique in learning Arabic vocabulary involves educators or students describing the meaning of vocabulary through body movements which must then be guessed by other students. The effect of mime technique assistance in learning Arabic vocabulary is that it can increase student learning motivation, increase student understanding and vocabulary mastery, and improve students' ability to speak Arabic.